Knowledge creation in networks of interorganizational cooperation - Balestrin, Alsones (2005)
This article describes how knowledge is generated in a network of small and medium sized companies in the garment industry located in the Brazilian southernmost state of Rio Grande do Sul. The central tie is provided by Agivest, an association of the garment industry. The findings point to a cooperative network where several “spaces” are created for knowledge sharing and exchange of experiences. Actually it is a learning network where generation of knowledge is perceived as a collective rather than an individual process.